Investigation of antioxidant vitamins (A, E, C) and lipid peroxidation levels in rats injected N-(1,3-benzothiazol-2-yl)-N-(4,5-dihydro-1H-imidazol-2-yl) amine - Karatas, F; Kara, H; Servi, S; Tug, T; Erulas, FA; Koca, M (Molecular Diversity Preservation International, 2005)
The present study examined the influence of synthetic N-(1,3-benzothiazol-2-yl)-N-(4,5-dihydro-1H-imidazol-2-yl) amine (2-Amdz) on levels of vitamins A, E and C and malondialdehyde (MDA) in rats. A total of 30 rats, divided into two groups, were used in the study. The control group was given only a subcutaneous injection of 250 mu L 75% ethanol, every other day. The other group of rats was administered a subcutaneous injection of 2-Amdz (25 mg kg(-1), dissolved in 250 mu L of 75% ethanol). Injections were continued for 16 days. After the application of 2-Amdz for 16 days, the serum levels of vitamins A, E and C and malondialdehyde (MDA) were determined by HPLC. The serum vitamin A, E, and C levels decreased significantly compared to controls (p < 0.05) whereas serum MDA levels were higher than control levels (p < 0.005). As a result, it can be suggested that 2-Amdz induced a severe stress and more importantly, increased the amount of free radicals and significantly decreased the levels of serum antioxidant vitamins.
Keywords: N-(1,3-benzothiazol-2-yl)-N-(4,5-dihydro-1H-imidazol-2-yl)amine; antioxidant vitamins; MDA and HPLC